Desarrollo de una propuesta de mejora para la planta de tratamiento de aguas residuales de la empresa AzulK S.A. (2019)
In this project he made a diagnosis of both the production process and the operation of the wastewater treatment plant of the company AZULK SA, later through a characterization the analysis was made of the conditions in which the residual water is coming out of the treatment , determining that the most critical parameter is that of fats and oils with average values of 400ppm for different conditions in the process, additionally, given that the DBO5 and DQO present values of 5976ppm and 4890ppm respectively, it is decided to take them into account throughout the project. To give a solution to this problem, we proceeded to review the bibliography to determine and present a proposal for improvement that will be adjusted to the company's requirements in terms of reagents and viability, which will achieve the removal and adjust all parameters to comply with the regulations. environmental protection, resolution 0631 of 2015.